Intercellular Sodium Regulates Repolarization in Cardiac Tissue with Sodium Channel Gain of Function - Nowak, Madison B. (Biophys J, 2020)
In cardiac myocytes, action potentials are initiated by an influx of sodium (Na(+)) ions via voltage-gated Na(+) channels. Na(+) channel gain of function (GOF), arising in both inherited conditions associated with mutation in the gene encoding the Na(+) channel and acquired conditions associated with heart failure, ischemia, and atrial fibrillation, enhance Na(+) influx, generating a late Na(+) current that prolongs action potential duration (APD) and triggering proarrhythmic early afterdepolarizations (EADs). Recent studies have shown that Na(+) channels are highly clustered at the myocyte intercalated disk, facilitating formation of Na(+) nanodomains in the intercellular cleft between cells. Simulations from our group have recently predicted that narrowing the width of the intercellular cleft can suppress APD prolongation and EADs in the presence of Na(+) channel mutations because of increased intercellular cleft Na(+) ion depletion. In this study, we investigate the effects of modulating multiple extracellular spaces, specifically the intercellular cleft and bulk interstitial space, in a novel computational model and experimentally via osmotic agents albumin, dextran 70, and mannitol. We perform optical mapping and transmission electron microscopy in a drug-induced (sea anemone toxin, ATXII) Na(+) channel GOF isolated heart model and modulate extracellular spaces via osmotic agents. Single-cell patch-clamp experiments confirmed that the osmotic agents individually do not enhance late Na(+) current. Both experiments and simulations are consistent with the conclusion that intercellular cleft narrowing or expansion regulates APD prolongation; in contrast, modulating the bulk interstitial space has negligible effects on repolarization. Thus, we predict that intercellular cleft Na(+) nanodomain formation and collapse critically regulates cardiac repolarization in the setting of Na(+) channel GOF.